2019
DOI: 10.1002/ceat.201800746
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Mechanisms and Rates of Cyclopentane Hydrates Formation in Brine

Abstract: Clathrate hydrates most often grow at the interface between liquid water and another fluid phase (hydrocarbon) acting as a provider for the hydrate guest molecules, and some transfer through this shell is required for the hydrate growth to proceed, thus self-limiting the reaction rate. An optical microscope and a horizontal reaction cell are utilized to capture the shell growth phenomenology and to estimate the hydrate layer growth rates from sequential pictures. Cyclopentane (CP) is chosen as the hydrate-form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…Xu et al [70,124] indicated that the duration of CPH formation from salty water decreases with both the increase of subcooling and agitation speed. Martinez de Baños et al [72] and Ho-Van et al [123] reported that the hydrate growth rate is observed to be proportional to subcooling.…”
Section: Subcooling and Agitationmentioning
confidence: 98%
“…Xu et al [70,124] indicated that the duration of CPH formation from salty water decreases with both the increase of subcooling and agitation speed. Martinez de Baños et al [72] and Ho-Van et al [123] reported that the hydrate growth rate is observed to be proportional to subcooling.…”
Section: Subcooling and Agitationmentioning
confidence: 98%
“…In pure water, gas hydrates nucleate at gas–water interfaces where gas solubility is orders of magnitude higher in the bulk phase. , Under quiescent conditions, it leads to the formation of a hydrate film at the interface, which then hinders gas–water contact and stops itself from thickening. Therefore, only micrometer-thick hydrate films are often observed at the gas–water interfaces. When agitations apply, gas hydrates still nucleate at the gas–water interfaces. However, turbulent conditions break the hydrate films and convey hydrate fragments (nuclei) into the bulk phase where they grow further into big masses …”
Section: Brief Descriptions Of Gas Hydrate Formationmentioning
confidence: 99%
“…The reduction in the hydrate growth rates due to the presence of salts is similar to the findings observed by previous researchers (for polycrystalline growth). 24,[44][45][46] In these experiments, NaCl salt dissociates in the water into Na + and Cl − ions due to the attraction towards water molecule dipoles via strong Coulombic interactions, forming clustering of the ions. 1,47,48 This strong attraction causes the inhibition effect to the hydrate formation, as the consequence of the water molecules being more attracted to the Na + and Cl − ions than to the hydrate structure.…”
Section: Effect Of Nacl On the Crystal Growth Rate And Morphologymentioning
confidence: 99%
“…Naeji and Varaminian utilized differential scanning calorimetry (DSC) to study THF hydrate with sodium chloride, and found that hydrate formation is inhibited with the phase change temperature shifted to a lower temperature, and a decrease in the heat of formation when salt is present in the system. 23 Ho-Van et al 24 measured cyclopentane hydrate growth in different saline solutions using optical microscopy. Their results showed that the measured cyclopentane hydrate growth rates decrease with increasing salt concentrations.…”
Section: Introductionmentioning
confidence: 99%